Sailing global health initiative ships into stormy seas: navigating the introduction of the Global Financing Facility in Mozambique - Andes Chivangue; Mary V. Kinney; Damiano Stella; Denise Namburete; Asha S. George (Global Health Action, 2025)
Background Mozambique joined the Global Financing Facility (GFF), a financing mechanism to accelerate progress for women, children, and adolescents’ health, with a history of donor dependence, distrust in public finances, and social inequities. Few independent studies have assessed the GFF. Objectives To understand how a global mechanism, such as the GFF, was introduced and utilized in Mozambique. Methods This qualitative study explored the aid coordination dynamics between 2015 and 2020 linked to the development of the Investment Case (IC) and Project Appraisal Document (PAD), key national GFF planning documents, based on data from 25 documents and 14 qualitative interviews thematically analyzed. Results The GFF was not fully understood by stakeholders and initially gained traction in the name of strengthening the health system, ironically amidst prevailing distrust of government systems. Some viewed the IC as consultatively developed, aiding the Ministry of Health in prioritizing issues and convening donors, while others remained sceptical about its impact. The PAD was viewed as a less consultative process, though it engaged the government and partners in setting disbursement-linked indicators (DLIs) to incentivize health system improvements. However, some stakeholders viewed them as unfeasible, while others were excluded by technical discourse. The perceived transparency issues around DLIs fuelled scepticism. Conclusion Although the GFF policy processes provided a technically alluring basis for addressing Mozambique’s health disparities, respondents revealed nuanced perspectives about how IC and PAD were formulated and followed. Aid coordination reflects various interdependencies, power dynamics, and uncertainties that require active relationship management and long-term institution building.